Phenotypic characterization and virulence-related properties of Escherichia albertii strains isolated from children with diarrhea in Brazil - Lima, Mauricio P.; Yamamoto, Denise; de Mello Santos, Ana Carolina; Ooka, Tadasuke; Hernandes, Rodrigo T. [UNESP]; Vieira, Mônica A.M.; Santos, Fernanda Fernandes; Silva, Rosa Maria; Hayashi, Tetsuya; Gomes, Tânia A.T. (Oxford University Press (OUP), 2019)
Escherichia albertii are emerging enteropathogens, whose identification is difficult, as they share biochemical characteristics and some virulence-related genes with diarrheagenic Escherichia coli (DEC). Studies on phylogeny, phenotypic characteristics and potential virulence factors of human E. albertii strains are scarce. In this study, we identified by multiplex PCR five E. albertii among 106 strains isolated from diarrheic children in São Paulo, Brazil, which were previously classified as atypical enteropathogenic E. coli. All strains were investigated regarding their phylogeny, biochemical properties, virulence-related properties, antimicrobial resistance and presence of putative virulence-related genes. All strains belonged to different E. albertii lineages and adhered to and produced attaching and effacing lesions on HeLa cells. Three strains invaded Caco-2 cells, but did not persist intracellularly, and three formed biofilms on polystyrene surfaces. All strains were resistant to few antibiotics and only one carried a self-transmissible resistance plasmid. Finally, among 38 DEC and 18 extraintestinal pathogenic E. coli (ExPEC) virulence-related genes searched, six and three were detected, respectively, with paa and cdtB being found in all strains. Despite the limited number of strains, this study provided additional knowledge on human E. albertii virulence potential, showing that they share important virulence factors with DEC and ExPEC.
Keywords: Antibiotic resistance; Diarrhea; Escherichia albertii; Phenotypic characteristics; Virulence genes; Virulence mechanisms